When Does the Muḍghah Become a Living Soul? The Framework of Fetal Protection by Sunnī Legal Schools in Light of Hellenistic as well as Judeo-Christian Traditions - Surjányi, Dávid (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
Due to the general practice of calling Islam an ‘Abrahamic religion’, many assume (and actually the majority of Muslims would assume) that the Muhammadan religion’s relationship with the issue of fetal protection and the practice of abortion reflects the conservative spirit of the Bible. However, nor the primary Muslim texts, nor the practice of Sunnī legal schools substantiate this assumption. In fact, in this comparative textual analysis I intend to show that Islamic jurisprudence resulted in homogeneous adjudication regarding abortion, just like the practice of Muslim states reflect versatile legislation. The end result is that most Sunnī schools of law allow first trimester abortions (and in some instances even further), something which reflects Aristotelian ‘pragmatism’ much more than the values of Judeo-Christian culture.